Coping with cancer: A qualitative study of adolescent and young adult perspectives. Issue 4 (April 2022) - Bradford, Natalie; Cashion, Christine; Holland, Lucy; Henney, Rosyln; Walker, Rick
Abstract: Objectives: Cancer can have long-term biopsychological impacts for young people that persist for years. To promote adjustment, it is essential to understand how young people cope, yet this is relatively understudied. Methods: This study explored the coping strategies using semi-structured interviews with 16 young people with cancer aged 15–24 years. Eligible participants were diagnosed within the previous 24 months and recruited through Australian Youth Cancer Services. Transcribed interviews were analysed using content analysis. Results: Coping strategies included: seeking support; controlling the focus; avoiding negatives and staying positive; meaning making and; changes with time. During treatment, seeking support, focussing on the present, distraction and avoidance were commonly applied. Following treatment, planning for the future, avoidance of re-traumatising situations and meaning making were used. Conclusion: Findings support the concept of coping as a dynamic process where different strategies are used depending on the stressor, available resources and previous experiences. Practice Implications: Comprehensive, developmentally appropriate psychosocial assessments, open communication, education and information provision, as well as appropriate referral for support are essential, particularly for young cancer survivors identified at risk. Highlights: Cancer diagnosed as a youth can have negative effects that persist for years after treatment. Young people describe using a variety of coping strategies, but may not always ask for, or accept support. Comprehensive psychosocial assessment and referral to support is essential, and should be offered during and beyond treatment.